Irene Dalis wedding photographs
Contact sheet of the Irene Dalis and George Loinaz wedding. Photographs include reception pictures of the bride and groom sitting at a table with Mary Gray Lauk, Irene's parents Mamie Rose (Boitano) Dalis and Peter Nicolas Dalis, the couple cutting the wedding cake, and Irene feeding it to George.